Preaching Must Die! : Troubling Homiletical Theology - Myers, Jacob D. (Project Muse, 2018)
The real question for homiletics in our increasingly postmodern, post-Christian contexts is not how we are going to prevent preaching from dying, but how we are going to help it die a good death. Preaching was not made to live. At most, preaching is a witness, a sign, a crimson X marking a demolition site. The church has developed sophisticated technologies in modernity to give preaching the semblance of life, belying the truth: preaching was born under a death sentence. It was born to die. Only when preaching embraces its own death is it able to live. This book, then, is a bold homiletical manifesto against preaching in support of preaching, and beyond preaching to the entire worship experience. It troubles modern homiletical theologies in light of the trouble always already at work within preaching. Hereby, it supports a way of preaching--and teaching preaching--that moves counter to the "wisdom of this world." It aims to joins in God's self-revealed counterlogic of superabundance that saturates and thereby breaks open worldly systems of thought and practice. The purpose of this book is to expose preaching to its own death-to help it embrace its death-so that it can discover what eternal and abundant life might look and feels like.